2009
DOI: 10.2478/s11756-009-0191-7
|View full text |Cite
|
Sign up to set email alerts
|

A new species of water mite Atractides (Atractides) turcicus sp. n. (Acari: Hydrachnidia: Hygrobatidae) from Turkey

Abstract: In this study, the structural characteristics, unique features, various organ measurements of males and females of the water mite Atractides (Atractides) turcicus sp. n. from Turkey are described. In addition, the study compares their characteristics with related species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 3 publications
(8 reference statements)
1
6
0
Order By: Relevance
“…This in turn has increased the eutrophication in the lake a lot. As a result, the amount of oxygen in the lake has decreased quite a lot which in turn has resulted in putting species with low oxygen tolerance under pressure [11]. The fact that the water mite species discovered within the scope of our study and found in Eber Lake are such which are found on the surface areas of pelagic regions proves this point.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…This in turn has increased the eutrophication in the lake a lot. As a result, the amount of oxygen in the lake has decreased quite a lot which in turn has resulted in putting species with low oxygen tolerance under pressure [11]. The fact that the water mite species discovered within the scope of our study and found in Eber Lake are such which are found on the surface areas of pelagic regions proves this point.…”
Section: Discussionsupporting
confidence: 54%
“…Table 1 indicates that the number of water mite species detected in Karamık Lake are at the expected level while the number for Eber Lake is far below the expected level. In terms of habitats, the species inhabiting Eber Lake were surface species [11]. The fact that the number of species discovered in Karamık Lake indicates that the lake is in a state of ecologic balance and that the species establishing the limnofauna are not about to be seriously threatened in the near future.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Remarks: Due to the strongly projected ventrodistal protrusion on P-2 and similar morphology of I-L (I-L-5 with short, equally rod-shaped sword setae and the stout, slightly modified I-L-6), the male of new species resembles Atractides dentipalpis (Walter, 1935) and A. turcicus Aşçı, 2009. Atractides dentipalpis was originally described from Algeria on the basis of a female specimen (Walter, 1935). Later, Boyacı (2007) reported A. dentipalpis from Isparta, Türkiye on the basis of both female and male sexes, and presented the first description of the male.…”
Section: Family: Torrenticolidae Piersig 1902mentioning
confidence: 99%